2021
DOI: 10.1183/23120541.00441-2021
|View full text |Cite
|
Sign up to set email alerts
|

Home monitoring of physiology and symptoms to detect interstitial lung disease exacerbations and progression: a systematic review

Abstract: BackgroundAcute exacerbations and disease progression in interstitial lung disease (AE-ILD) pose important challenges to clinicians and patients. AE-ILD are variable in presentation but may result in rapid progression of ILD, respiratory failure and death. However, in many cases AE-ILD may go unrecognised so that their true impact and response to therapy is unknown. The potential for home monitoring to facilitate early, and accurate, identification of AE and/or ILD progression has gained interest. With increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 87 publications
2
22
0
Order By: Relevance
“…A systematic review has shown that patient adherence to home spirometry was satisfactory (> 75%) and values measured at home correlated significantly with those measured in-hospital ( 26 ) Interestingly, the variability in home-measured FVC values may actually be an independent predictor for fibrotic ILD progression ( 27 ) Increasing adherence can be achieved by setting up automated email reminders when a measurement is not performed when expected ( 28 ), providing comprehensive initial and refresher training to patients, or using a spirometry schedule which is more acceptable (rather than daily measurements) ( 29 ). The optimal timing and frequency of testing to account for diurnal variation has not yet been established ( 30 ).…”
Section: Current and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review has shown that patient adherence to home spirometry was satisfactory (> 75%) and values measured at home correlated significantly with those measured in-hospital ( 26 ) Interestingly, the variability in home-measured FVC values may actually be an independent predictor for fibrotic ILD progression ( 27 ) Increasing adherence can be achieved by setting up automated email reminders when a measurement is not performed when expected ( 28 ), providing comprehensive initial and refresher training to patients, or using a spirometry schedule which is more acceptable (rather than daily measurements) ( 29 ). The optimal timing and frequency of testing to account for diurnal variation has not yet been established ( 30 ).…”
Section: Current and Future Directionsmentioning
confidence: 99%
“…Home spirometry allows for trends in lung function decline to be generated, which is of great importance in monitoring and increasing diagnostic accuracy for PF-ILD. Additionally, as many patients could not be seen often enough during the pandemic, a role emerged for home spirometry to aid with early diagnosis of acute exacerbations of ILD ( 26 ).…”
Section: Current and Future Directionsmentioning
confidence: 99%
“…3 Evidence for home-monitoring in managing ILD has increased in recent years, with home-spirometry gaining attention. 4,5 Despite technical issues, 5 studies have demonstrated that home-spirometry can predict outcomes by monitoring the rate of decline in FVC, and its measures correlate with hospital-spirometry. 2,4,6 A significant gap remains in the current literature; specifically, there is scant evidence supporting the benefit of continuous monitoring of both physiological parameters and symptoms in detecting progression or response to treatment.…”
mentioning
confidence: 99%
“…These findings agree with previously published studies, which indicated that cardiovascular parameters, including HR, can reflect changes in physiological conditions. 4 A future area of interest will be to explore the relationship of physiological, imaging and serum biomarkers with home spirometry to ensure early and accurate stratification of patients and prediction of outcomes. When assessing fatigue, the progressed group showed an increased mean FSS.…”
mentioning
confidence: 99%
See 1 more Smart Citation